Molding Work in Fixed Prosthesis (Revista Nacional de Odontología, 2019)
Introduction: molding is a fundamental step in a prosthetic rehabilitation treatment. It is the transfer of the clinical situation to the dental laboratory. There are numerous molding materials. Among them, we highlight the elastomers, which are non-aqueous elastic materials. They are: silicone polymerized by addition, silicone polymerized by condensation, polyether and polysulfide. The objective of this work is to present what is in the most updated literature pertinent to the subject, which includes a new reality for impressions of work in fixed prosthesis.Methodology: the bibliographic survey was carried out using the electronic databases SciELO, Bireme and PubMed, using the keywords dental prosthesis; dental impression materials; dental impression technique and fixed prosthesis. Articles that included information relevant to the proposed theme were included.Result: Regarding the dimensional stability of these materials, the most stable is the addition silicone, followed by polyether, polysulfide and, finally, condensation silicone. For the use of these materials, the dentist must have some impression techniques: impression technique with individual cap, repackaging or double printing technique, repacking technique with the use of previous relief and simultaneous or double mixing technique.Conclusion: there is no consensus in the literature that elucidates which material and, mainly, the technique that should be recommended for performing the work impression. To minimize the issue, the professional must define which technique will be followed according to his ability, respecting his limitations and security regarding the procedure.
Keywords: prótese dentária; materiais para moldagem odontológica; técnica de moldagem odontológica; prótese fixa